Gender stereotypes, motivation, and career aspirations of women in an undergraduate group (Management and Connections Journal, 2026)
This paper aims to investigate the gender stereotypes and their consequences within the organizational context. A case study was conducted applying semi-structured interviews. The interviews were transcribed and subjected to content analysis using NVIVO software. The presence of gender stereotypes was evidenced. However, contrary to the classical literature on gender, the presence of gender stereotypes does not directly affect the motivation and career aspirations of women. On the contrary, the present article highlights a preference for a more participative transformational leadership, which is more characteristic of feminine leadership, leading us to suggest that the gap pointed out by the Role Congruity Theory may be closing. The article provides a different perspective regarding the impact of gender issues on leadership by considering advancements in studies on leadership in response to a more complex corporate world and the characteristics of the Generation-Z individuals that will constitute the new generation of corporate leaders.
Keywords: Generation Z; female leadership; gender stereotypes; motivation; career aspiration